The Impact of Export Destination Policies to East Asia and Pacific on GDP per Capita - Susanto, Eko Joko; Khoirunorrofik, Khoirunorrofik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
East Asia and the Pacific region has been the second-largest trading bloc in the world for the past 40 years, following Europe, with a steadily increasing transaction value trend. In contrast, Europe, which has the highest trade levels globally, has shown no significant growth over the past four decades and has even experienced a slight decline. East Asia and the Pacific provide access to a diversified market with efficient technology transfer, which is believed to have a positive impact on GDP per capita growth. This study analyzes the impact of export destination policies to East Asia and the Pacific on GDP per capita by comparing sample countries from the Upper Middle Income (UMI) and Lower Middle Income (LMI) groups. The study employs a dynamic panel System GMM (Arellano-Bond 2-step) method, which combines level and first-difference equations for greater efficiency while using instrumental variables to capture endogeneity, mitigate heteroskedasticity, and address serial correlation in the model. The regression results indicate that exports to East Asia and the Pacific contribute to an increase in GDP per capita by an average of 0.016% for every 1% increase in export proportion to this region, ceteris paribus, in Upper Middle Income countries. However, the impact is insignificant and non-linear for Lower Middle Income countries. Furthermore, there is no strong evidence that export destinations to Europe and Central Asia, South Asia, Latin America, the Arab region, or Sub-Saharan Africa are significantly correlated with GDP per capita in either income group. The results of multicollinearity tests, AR(2) tests, and Hansen tests confirm the absence of multicollinearity, serial correlation, and that the instruments used in the model are valid.